MENCEGAH KORUPSI DI DAERAH DENGAN PENGAWALAN OLEH KEJATI - Florentinus Sudiran (Universitas 17 Agustus 1945 Samarinda, 2017)
The aim of this research is to know,(1) The control of the high court in East Kalimantan province on the multy years Contract projects with the sum Rp.2.38 trylion (2) The team of the court is surely controlling the MYC projects (3) If any difficulty the team will give legal opinion,(4) The team will involve the Inspectorate here,(5) Both will meet once a month.The suggestions are (1)The team has to control in the field,(2) The meeting for both has to be reaalized , (3) Both are truly working together,(3) To do any way to avoid the corruption , (4) If any corruption has to be sentenced whoever ,(5) Both have to keep neutral anyway.